The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Fossil leaf cuticle: Best practices for preparation and paleo-CO2 analysis - Xiaoqing Zhang; Dana L. Royer; Carina E. Colombi; Juan Martin Drovandi; Jennifer C. McElwain; Gaëtan Guignard; Qin Leng; Barry H. Lomax; Nathan D. Sheldon; Rebekah A. Stein; Garland R. Upchurch; Yongdong Wang; et al. (Earth-Science Reviews, 2025)

Positive Feedback on Climate Warming by Stream Microbial Decomposers Indicated by a Global Space‐For‐Time Substitution Study - Javier Pérez; Luz Boyero; Richard G. Pearson; Mark O. Gessner; Alan Tonin; Naiara López‐Rojo; Juan Rubio‐Ríos; Francisco Correa‐Araneda; Alberto Alonso; Aydeé Cornejo; Ricardo J. Albariño; Sankarappan Anbalagan; et al. (Global Change Biology, 2025)
Decomposition of plant litter is a key ecological process in streams, whose contribution to the global carbon cycle is large relative to their extent on Earth. We examined the mechanisms underlying the temperature sensitivity (TS) of instream decomposition and forecast effects of climate warming on this process. Comparing data from 41 globally distributed sites, we assessed the TS of microbial and total decomposition using litter of nine plant species combined in six mixtures. Microbial decomposition conformed to the metabolic theory of ecology and its TS was consistently higher than that of total decomposition, which was higher than found previously. Litter quality influenced the difference between microbial and total decomposition, with total decomposition of more recalcitrant litter being more sensitive to temperature. Our projections suggest that (i) warming will enhance the microbial contribution to decomposition, increasing CO 2 outgassing and intensifying the warming trend, especially in colder regions; and (ii) riparian species composition will have a major influence on this process.

Integrated membrane packed enzymatic column for the removal of atrazine in wastewater: Experimental, kinetics, breakthrough curves analysis and applicability in real wastewater - Mahadi Lesaoana; Mbongiseni Dlamini; Dean Brady; Roger Sheldon; Heidi Richards (Journal of Water Process Engineering, 2024)

Distribution of Organohalogen and Synthetic Musk Compounds in Breast Adipose Tissue of Breast Cancer Patients in Ulster County, New York, USA - Adela Jing Li; Sheldon M. Feldman; Richard K. McNally; Kurunthachalam Kannan (Archives of Environmental Contamination and Toxicology, 2019)

Biogeographical patterns of blood parasite lineage diversity in avian hosts from southern Melanesian islands - Farah Ishtiaq; Sonya M. Clegg; Albert B. Phillimore; Richard A. Black; Ian P. F. Owens; Ben C. Sheldon (Journal of Biogeography, 2010)
Aim (1) To describe the species–area relationships among communities of Plasmodium and Haemoproteus parasites in different island populations of the same host genus (Aves: Zosterops ). (2) To compare distance–decay relationships (turnover) between parasite communities and those with potential avian and dipteran hosts, which differ with respect to their movement and potential to disperse parasite species over large distances. Location Two archipelagos in the south‐west Pacific, Vanuatu and New Caledonia ( c . 250 km west of Vanuatu) and its Loyalty Islands, with samples collected from a total of 16 islands of varying sizes (328–16,648 km 2 ). Methods We characterized parasite diversity and distribution via polymerase chain reaction (PCR) from avian ( Zosterops ) blood samples. Bayesian methods were used to reconstruct the parasite phylogeny. In accordance with recent molecular evidence, we treat distinct mitochondrial DNA lineages as equivalent to species in this study. Path analysis and parasite lineage accumulation curves were used to assess the confounding effect of inadequate sampling on the estimation of parasite richness. Species–area and species–distance relationships were assessed using linear regression: distance–decay relationships were assessed using Mantel tests. Results Birds and mosquito species and Plasmodium lineages exhibited significant species–area relationships. However, Plasmodium lineages showed the weakest ‘species–area’ relationship; no relationship was found for Haemoproteus lineages. Avian species richness influenced parasite lineage richness more than mosquito species richness did. Within individual avian host species, the species–area relationship of parasites showed differing patterns. Path analysis indicated that sampling effort was unlikely to have a confounding effect on parasite richness. Distance from mainland (isolation effect) showed no effect on parasite richness. Community similarity decayed significantly with distance for avifauna, mosquito fauna and Plasmodium lineages but not for Haemoproteus lineages. Main conclusions Plasmodium lineages and mosquito species fit the power‐law model with steeper slopes than found for the avian hosts. The lack of species–distance relationship in parasites suggests that other factors, such as the competence of specific vectors and habitat features, may be more important than distance. The decay in similarity with distance suggests that the sampled Plasmodium lineages and their potential hosts were not randomly distributed, but rather exhibited spatially predictable patterns. We discuss these results in the context of the effects that parasite generality may have on distribution patterns.

In Vitro–In Vivo Correlation on Delivery of Drug Candidates to Articular Cartilage - Qin Wang; Sonya Glasson; Uma Raut; Jamie Emerson; Tracey Blanchet; Gary Bridson; Richard Sheldon; Nevena Mollova; Elisabeth Morris; Xin Xu; Vikram S. Patel (Pharmaceutical Research, 2008)

Determination of apparent quantum yield spectra for the formation of biologically labile photoproducts - William L. Miller; Miller Moran; Wade M. Sheldon; Richard G. Zepp; Stephen Opsahl (Limnology and Oceanography, 2002)
Quantum yield spectra for the photochemical formation of biologically labile photoproducts from dissolved organic matter (DOM) have not been available previously, although they would greatly facilitate attempts to model photoproduct formation rates across latitudinal, seasonal, and depth‐related changes in spectral irradiance. Apparent quantum yield spectra were calculated for two coastal environments from the southeastern United States using postirradiation bacterial respiration as a measure of total labile photoproduct formation and a cutoff filter method to model spectral dependence. As has been the case for previously studied classes of DOM photoproducts (i.e., dissolved inorganic carbon, CO, and H 2 O 2 ), ultraviolet (UV)‐B irradiance was significantly more efficient at forming labile photoproducts (i.e., compounds readily assimilated by marine bacterioplankton) than UV‐A and visible irradiance. Calculations of DOM photoproduct formation in southeastern U.S. coastal surface waters indicate a formation ratio for biologically labile photoproducts :CO of 13 : 1. The slope of a natural log plot of the apparent quantum yield spectrum obtained for biologically labile photoproducts was similar to that for CO (0.028 nm −1 vs. 0.034 nm −1 ). Modeled kinetic rates therefore indicate that the production ratio of these photoproduct classes is approximately maintained despite variations in the solar spectrum that occur with depth in a water column or distance from shore. Application of the apparent quantum yield to coastal regions worldwide predicts an annual formation rate of biologically labile photoproducts in coastal waters of 206 × 10 12 g C.

Carbon loss and optical property changes during long‐term photochemical and biological degradation of estuarine dissolved organic matter - Mary Ann Moran; Wade M. Sheldon; Richard G. Zepp (Limnology and Oceanography, 2000)
Terrestrially derived dissolved organic matter (DOM) impacts the optical properties of coastal seawater and affects carbon cycling on a global scale. We studied sequential long‐term photochemical and biological degradation of estuarine dissolved organic matter from the Satilla River, an estuary in the southeastern United States that is dominated by vascular plant‐derived organic matter. During photodegradation, dissolved organic carbon (DOC) loss (amounting to 31% of the initial DOC) was much less extensive than colored dissolved organic matter (CDOM) or fluorescent dissolved organic matter (FDOM) loss (50% and 56% of the initial CDOM and FDOM), and analysis of kinetics suggested a reservoir of DOC that was resistant to photodegradation. In contrast, CDOM photodegradation closely followed first‐order kinetics over two half‐lives with no indication of a nondegradable component. FDOM loss was slightly biased toward fluorophores considered representative of terrestrial humic substances. Additional changes in optical properties included increases in spectral slope and shifts in fluorescence excitation/emission maxima that were generally consistent with previous observations from field studies of photobleached DOM. Biological degradation of photobleached DOM was more rapid than that of unbleached material, and this net positive effect was evident even for extensively photodegraded material. Bacterial degradation caused shifts in the opposite direction from photochemical degradation for both spectral slope and excitation/emission maxima and thus dampened but did not eliminate changes in optical properties caused by photobleaching.